1988
DOI: 10.3758/bf03209064
|View full text |Cite
|
Sign up to set email alerts
|

Increase in retention of a taste aversion by weanling rats after a long interval

Abstract: Weanling rats were tested for retention of an aversion to a novel flavor (chocolate milk) that had been conditioned as a single-element conditioned stimulus (CS) or in compound with a novel ambient odor (banana). The presence of the ambient odor during conditioning had no effect on flavor aversion shortly thereafter, confirming previous results. The flavor aversion observed 21 days after conditioning, however, was significantly stronger for pups conditioned with the singleelement CS than for those given the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Thus, it is possible that methamphetamine enhanced the memory of aversive CS-US attributes, and therefore, facilitated strong retention of CTA relative to that observed with a non-amphetamine-based drug like LiCl that was used in studies reporting a decreased magnitude of responding following retention intervals in maturing rats (Steinert et al 1980; Guanowsky et al 1983). Overall, the present results are more similar to the findings reporting that memory for LiCl-induced CTA is intact after retention intervals that correspond to the maturation of motivational systems (Klein et al 1977; Kraemer et al 1988). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, it is possible that methamphetamine enhanced the memory of aversive CS-US attributes, and therefore, facilitated strong retention of CTA relative to that observed with a non-amphetamine-based drug like LiCl that was used in studies reporting a decreased magnitude of responding following retention intervals in maturing rats (Steinert et al 1980; Guanowsky et al 1983). Overall, the present results are more similar to the findings reporting that memory for LiCl-induced CTA is intact after retention intervals that correspond to the maturation of motivational systems (Klein et al 1977; Kraemer et al 1988). …”
Section: Discussionsupporting
confidence: 91%
“…For example, Guanowsky et al (1983) reported that post-weanling (~PND 26) and adult rats acquired CTA after a single sucrose–LiCl pairing and the magnitude of the response was diminished after a 28-day retention interval in the maturing rats, but not in the adults (also see Ader and Peck, 1977; Steinert et al 1980; Misanin et al 1983). Other reports, however, suggest that postweanling rats (~PND 23) administered sucrose-LiCl or chocolate milk-LiCl pairings exhibited robust CTA when tested 21 and 28 days after acquisition (Klein et al 1977 and Kraemer et al 1988, respectively).…”
Section: Introductionmentioning
confidence: 93%
“…Because of the rapid elimination of ethanol, the unconditioned properties afforded by ethanol might be more short-lived in the 20-day-olds. This short duration of ethanol action might condition a weaker aversion to the sucrose (Goudie, 1987), and further training with this relatively weak US might be necessary to observe the conditioned aversion (Infurna, Steinert, Freda, & Spear, 1979; Kraemer, Lariviere, & Spear, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…For example, young animals do not show adults' inclination for overshadowing when they are tested on a single element of a compound training stimulus (Kraemer, Lariviere, & Spear, 1988;Mellon, Kraemer, & Spear, 1991) but rather show potentiation, the opposite of overshadowing (Hinderliter & Misanin, 1988;Kucharski & Spear, 1985;Spear & Kucharski, 1984). Age-related differences also exist in the treatment of contextual stimuli (Lariviere, Chen, & Spear, 1990; McKinzie, Lee, Bronfen, Spear, & Spear, 1994;Solheim, Hensler, & Spear, 1980).…”
mentioning
confidence: 99%